Identification of potent, selective KDM5 inhibitors. Issue 17 (1st September 2016) - Gehling, Victor S.; Bellon, Steven F.; Harmange, Jean-Christophe; LeBlanc, Yves; Poy, Florence; Odate, Shobu; Buker, Shane; Lan, Fei; Arora, Shilpi; Williamson, Kaylyn E.; Sandy, Peter; Cummings, Richard T.; et al.
Graphical abstract: Abstract: This communication describes the identification and optimization of a series of pan-KDM5 inhibitors derived from compound1, a hit initially identified against KDM4C. Compound1 was optimized to afford compound20, a 10 nM inhibitor of KDM5A. Compound20 is highly selective for the KDM5 enzymes versus other histone lysine demethylases and demonstrates activity in a cellular assay measuring the increase in global histone 3 lysine 4 tri-methylation (H3K4me3). In addition compound20 has good ADME properties, excellent mouse PK, and is a suitable starting point for further optimization.